Ablation of Survivin in T Cells Attenuates Acute Allograft Rejection after Murine Heterotopic Heart Transplantation by Inducing Apoptosis - Xu, Heng; Yu, Jizhang; Cui, Jikai; Chen, Zhang; Zhang, Xi; Zou, Yanqiang; Du, Yifan; Li, Yuan; Le, Sheng; Jiang, Lang; Xia, Jiahong; Wu, Jie (Frontiers in Immunology, 2021)
Although studies in oncology have well explored the pharmacological effects of Birc5, little is known about its role in allogeneic T-cell responses. Therefore, the present study used a mouse model of acute heart allograft rejection to investigate the protective effect and mechanism of conditional knockout of Birc5 in T cells. Survivin (encoded by Birc5) was up-regulated in T cells activated in vivo and in vitro. Deletion of Birc5 in T cells attenuated acute heart allograft rejection by reducing the ratio of effector to naive T cells and Th1 to Tregs. In addition, deletion of Birc5 had no noticeable effect on proliferation but rather on apoptosis and secretion of IFN-γ. The results revealed a significant increase in the percentage of Annexin V positive CD4+ T cells in the Birc5-/- group, compared to the WT. Moreover, there was significant increase in early apoptotic alloreactive T cells in Birc5-/- mice and this was partly mediated by caspase-3. Furthermore, treatment with YM155 inhibited acute heart allograft rejection in vivo and increased T-cell apoptosis in healthy human PBMCs in vitro. The results highlight a potential therapeutic target for the prevention and treatment of acute transplant rejection.